nCOVID-19 Pandemic: From Molecular Pathogenesis to Potential Investigational Therapeutics - Kabir, Md. Tanvir; Uddin, Md. Sahab; Hossain, Md. Farhad; Abdulhakim, Jawaher A.; Alam, Md. Asraful; Ashraf, Ghulam Md; Bungau, Simona G.; Bin-Jumah, May N.; Abdel-Daim, Mohamed M.; Aleya, Lotfi (Frontiers in Cell and Developmental Biology, 2020)
In December 2019, a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-related epidemic was first observed in Wuhan, China. In 2020, owing to the highly infectious and deadly nature of the virus, this widespread novel coronavirus disease 2019 (nCOVID-19) became a worldwide pandemic. Studies have revealed that various environmental factors including temperature, humidity, and air pollution may also affect the transmission pattern of COVID-19. Unfortunately, still, there is no specific drug that has been validated in large-scale studies to treat patients with confirmed nCOVID-19. However, remdesivir, an inhibitor of RNA-dependent RNA polymerase (RdRp), has appeared as an auspicious antiviral drug. Currently, a large-scale study on remdesivir (i.e. 200 mg on first day, then 100 mg once/day) is ongoing to evaluate its clinical efficacy to treat nCOVID-19. Good antiviral activity against SARS-CoV-2 was not observed with the use of lopinavir/ritonavir (LPV/r). Nonetheless, the combination of umifenovir and LPV/r was found to have better antiviral activity. Furthermore, a combination of hydroxychloroquine (i.e. 200 mg 3 times/day) and azithromycin (i.e. 500 mg on first day, then 250 mg/day from day 2-5) also exhibited good activity. Currently, there are also ongoing studies to evaluate the efficacy of teicoplanin and monoclonal and polyclonal antibodies against SARS-CoV-2. Thus, in this article, we have analyzed the genetic diversity and molecular pathogenesis of nCOVID-19. We also present possible therapeutic options for nCOVID-19 patients.